American Journal of Political Science (JSTOR)
The American Journal of Political Science (AJPS), published four times each year, is one of the most widely-read political science journals in the United States. AJPS is a general journal of political science open to all members of the profession and to all areas of the discipline of political science. JSTOR provides a digital archive of the print version of American Journal of Political Science. The electronic version of American Journal of Political Science is available at http://www.blackwell-synergy.com/servlet/useragent?func=showIssues&code=ajps. Authorized users may be able to access the full text articles at this site.
Keywords: American Studies